Self-Expandable Metal Stent for Malignant Colonic Obstruction: Outcome in Proximal vs. Left Sided Tumor Localization - Tal, A. O.; Friedrich-Rust, M.; Bechstein, W. O.; Woeste, G.; Trojan, J.; Zeuzem, S.; Sarrazin, C.; Albert, J. G. (Zeitschrift für Gastroenterologie, 2013)
Introduction: The aim of this study was to evaluate the outcome of through-the-scope (TTS) implanted self-expanding metal stent (SEMS) comparing left-sided vs. proximal placement with regard to complications and outcome in palliation of malignant colorectal obstruction.Material and Methods: All patients were consecutively retrospectively enrolled to this study between January 2009 and February 2012 due to impending or prevalent complete malignant colorectal obstruction. TTS applicable uncovered nitinol SEMS with unique flexible properties were used (Taewoong Medical, South Korea). Left-sided obstruction (aboral from the left flexure) was compared to proximal (from the ileo-cecal valve to the left flexure) localization. All patients have been discussed in the interdisciplinary tumor conference and the recommendation to treat by endoscopic stent placement was given in consensus.Results: A total of 15 patients was enrolled to this study (10 male and 5 female; mean age 68.3 ± 15.4 years, range 48 − 94), five patients with obstructions located in the proximal hemicolon whereas ten patients had a left-sided malignancy. Technical success was achieved in all cases and there was no early complication noticed. Three late complications included tumor overgrowth (n = 1), stent occlusion (1), and dislocation (1). Stent-in-stent insertion achieved, again, clinical success. The site of SEMS implantation (proximal vs. left colon) had no impact on patient outcome or complication rate. SEMS patency duration was 269.8 ± 175.2 days (range 30 − 570) and mean survival of the patients was 305.1 ± 279.3 days (range 16 − 990).Conclusion: TTS application of flexible, non-covered SEMS seems to be safe and effective for palliation of malignant colorectal obstruction independent of localization of the tumor in the colon.
Keywords: kolorektales Karzinom; Kolon; selbst expandierende Metallstents; Endoskopie; maligne Kolonstenosen; Kolonoskopie